Reproductive effects of maternal metabolic disorders: Implications for pediatrics and obstetrics - Levy, Harvey L. (The Turkish Journal of Pediatrics, 1996)
The reproductive effects of metabolic disorders in women can be divided into four categories. The first of these is infertility. Galactosemia with its complication of ovarian failure is the disorder in this category. This complication may be prenatal in origin but whether this is so and its cause are unknown. The second category includes pregnancy effects of maternal metabolic disorders. The urea cycle disorder ornithine transcarbamylase (OTC) deficiency, maternal maple syrup urine disease and maternal homocystinuria are in this category. In the first two disorders, postpartum life-threatening illness due to metabolic crisis has occurred. Maternal homocystinuria is associated with a high risk for postpartum thromboembolic complications. The third category is the pregnancy effect of a fetal metabolic disorder. Pregnancies in which the fetus had long-chain hydroxyacyl-CoA dehydrogenase deficiency (LCHADD) have been complicated by the life-threatening (HELLP) syndrome during the third trimester. Rapid recovery of the mothers followed delivery, on occasion by emergency cesarean section. The fourth category is the fetal effects (teratogenicity) from a maternal metabolic disorder. The best-known example of this is maternal phenylketonuria (PKU), which produces microcephaly, mental retardation, congenital heart disease and intrauterine growth retardation. Treatment with a low phenylalanine diet begun before conception or no later than the earliest weeks of the first trimester markedly reduces the risk to the fetus and can result in normal offspring. Other examples of teratogenicity may include maternal homocystinuria and maternal hypothyroidism.
Keywords: maternal metabolic disorder; fetus; reproduction; maternal PKU